Influence of Life Meaning on Subjective Well-Being of Older People: Serial Multiple Mediation of Exercise Identification and Amount of Exercise - Zhang, Qi; Yang, Yang; Zhang, Guo-Li (Frontiers in Public Health, 2021)
Objective: This study aimed to explore the relationship between life meaning and subjective well-being among older people and the mediating role of subjective exercise identification and objective amount of exercise. Methods: A total of 352 older respondents completed four questionnaires: the Chinese life meaning scale, the University of Newfoundland Happiness Scale, the physical activity habits questionnaire, and the exercise identification questionnaire designed for this study. Results: Gender differences existed in the respondents' perception of life meaning, and men had a better perception of life meaning (t = 2.28, SE = 0.63, p < 0.05). There were age differences in the subjective well-being of older people (F = 5.69, partial η2 = 0.03, p < 0.01); the subjective well-being of older individuals steadily declines with rising age. Life meaning not only directly affected the subjective well-being of the respondents but also indirectly influenced their subjective well-being through the following three pathways: life meaning → exercise identification → subjective well-being (mediating effect of 22%); life meaning → amount of exercise → subjective well-being (mediating effect of 22%); and life meaning → exercise identification → amount of exercise → subjective well-being (serial multiple mediation effect of 27%). Conclusion: The more positive the life meaning perception of older people is, the higher their experience of subjective well-being. For older people to sense the meaning of life, we recommend that they realize the importance of physical activities and take the initiative to engage in physical activities to obtain higher subjective well-being.